Temporal and spatial determination of solidification rate during pulsed laser beam welding of hot-crack susceptible aluminum alloys by means of high-speed synchrotron X-ray imaging - M. Seibold; K. Schricker; L. Schmidt; D. Diegel; H. Friedmann; P. Hellwig; F. Fröhlich; F. Nagel; P. Kallage; A. Rack; H. Requardt; Y. Chen; et al. (Journal of Advanced Joining Processes)
Pulsed laser beam welding is primarily used to join thin-walled components. The use of 6xxx group aluminum alloys is characterized by good mechanical properties but these alloys are prone to hot cracking during solidification, i.e., requirements regarding strength and tightness, as increasingly important for electromobility related applications, cannot be fulfilled. The solidification rate has been identified as dominant factor in pulsed conduction welding which can be adjusted by the pulse shape, i.e., by varying the beam power over time for a single pulse.Pulse shapes with different, linear ramp-down slopes were studied to describe the interaction between beam power and resulting solidification rate for spot welds. Based on rotationally symmetric conditions of the spot welds, the solidification rate can be measured in radial and vertical directions. The welding process of EN AW 6082 alloy was examined by in situ high-speed synchrotron X-ray imaging at the European Synchrotron Radiation Facility (ESRF) for this reason. Frame rates up to 120,000 Hz and subsequent image analysis allowed in-depth analysis of the solidification processes, their dependence on different spatial directions, and the resulting effects on hot crack formation.